Signaling Pathways that Mediate Skeletal Muscle Hypertrophy: Effects of Exercise Training - Fernandes, Tiago; Soci, Úrsula P.R.; Melo, Stéphano F.S.; Alves, Cléber R.; Oliveira, Edilamar M. (IntechOpen, 2012)
None